The pose of the author: colonial Africa and the operations of genre. (2nd January 2019) - Lahiri, Madhumita
ABSTRACT: Focusing on the 1920s publications of the Mozambican intellectual C. Kamba Simango (1890–1966), this article explores the transformations of a single story across the pages of amateur ethnomusicology (Natalie Curtis's Songs and Tales from the Dark Continent, 1920), African American children's literature (Jessie Redmon Fauset's The Brownies' Book, 1921), and professional anthropology (Franz Boas's Journal of American Folklore, 1922). In each instance, Simango's name and individual identity is crucial to the presentation of the text, yet the emphasis on the name does not necessarily indicate authorship, which instead emerges more strongly through the interaction of institutional norms, racial prestige, and genre expectations. The transnational author is thus formed through both genre and biography. Revising the formulations of Michel Foucault and Roland Barthes, I propose a performative notion of authorship that can reflect both the literary paradigm that desires individual expressivity and the ethnographic one that seeks collective culture.